Physical activity monitoring in Alzheimer’s disease during sport interventions: a multi-methodological perspective - Shari David; Christian Hohenfeld; Christian Hohenfeld; Christian Hohenfeld; Luisa Haberl; Jennifer Pahl; Ana S. Costa; Ana S. Costa; Ana S. Costa; Axel Kilders; Frank Hildebrand; Jörg B. Schulz; et al. (Frontiers in Neurology, 2023)
IntroductionAssessment methods for physical activity and fitness are of upmost importance due to the possible beneficial effect of physical conditioning on neurodegenerative diseases. The implementation of these methods can be challenging when examining elderly or cognitively impaired participants. In the presented study, we compared three different assessment methods for physical activity from the Dementia-MOVE trial, a 6-months intervention study on physical activity in Alzheimer’s disease. The aim was to determine the comparability of physical activity assessments in elderly participants with cognitive impairment due to Alzheimer’s disease.Material or methods38 participants (mean age 70 ± 7 years) with early-stage Alzheimer’s disease (mean MoCA 18.84 ± 4.87) were assessed with (1) fitness trackers for an average of 12 (± 6) days, (2) a written diary on daily activities and (3) a questionnaire on physical activity at three intervention timepoints. For comparison purposes, we present a transformation and harmonization method of the physical assessment output parameters: Metabolic equivalent of task (MET) scores, activity intensity minutes, calorie expenditure and moderate-to-vigorous physical activity (MVPA) scores were derived from all three modalities. The resulting parameters were compared for absolute differences, correlation, and their influence by possible mediating factors such as cognitive state and markers from cerebrospinal fluid.ResultsParticipants showed high acceptance and compliance to all three assessment methods. MET scores and MVPA from fitness trackers and diaries showed high overlap, whilst results from the questionnaire suggest that participants tended to overestimate their physical activity in the long-term retrospective assessment. All activity parameters were independent of the tested Alzheimer’s disease parameters, showing that not only fitness trackers, but also diaries can be successfully applied for physical activity assessment in a sample affected by early-stage Alzheimer’s disease.DiscussionOur results show that fitness trackers and physical activity diaries have the highest robustness, leading to a highly comparable estimation of physical activity in people with Alzheimer’s disease. As assessed parameters, it is recommendable to focus on MET, MVPA and on accelerometric sensor data such as step count, and less on activity calories and different activity intensities which are dependent on different variables and point to a lower reliability.